A Comparison of Learning Technologies for Teaching Spacecraft Software Development. (June 2014) - Straub, Jeremy
The development of software for spacecraft represents a particular challenge and is, in many ways, a worst case scenario from a design perspective. Spacecraft software must be "bulletproof" and operate for extended periods of time without user intervention. If the software fails, it cannot be manually serviced. Software failure may result in mission degradation or complete spacecraft loss. This article considers how learning technologies can be used to aid student understanding of spacecraft software design, to facilitate the creation of better spacecraft software. It presents a framework for comparing spacecraft software development learning technologies. It then evaluates and compares five prospective learning technologies based on this framework. The areas that each learning technology is particularly well suited for are presented and discussed.